Evaluation and Analysis of Available Transfer Capability in Deregulated Power System Environment - Dhana Sai Sri, M; Srinivasa Varma, P (International Journal of Engineering and Technology, 2018)
Reliability of network is need of the hour in the present power system market and is constrained by capability of the network. The network calculations are performed using accurate and high efficient strategies. In order to perform power transactions in the system, the computation of available transfer capability is essential which a metric of capability of the system. Generally, effect wattless power is not taken into account in the methodologies for computation of linear available transfer capability. In this paper, a methodology which considers the reactive power flows for enhancement of linear ATC is presented. In order to perform analysis theoretically, a standard IEEE 3 bus system is considered. Another case study i.e., 14 bus system available in IEEE test systems is used for simulation analysis. FACTS technology is incorporated in the existing system in order to enhance capability of the network. To facilitate transfer maximum power in the system, an optimal power-flow-based ATC enhancement model is formulated and presented along with simulation results. Studies based on the IEEE 3-bus system and 14-bus systems with TCSC demonstrate the effectiveness of FACTS control on ATC enhancement.Â Â